Advanced Optimal For Three Phase Rectifier in Power Electronic System - Salam Waley Shneen (Institute of Advanced Engineering and Science, 2018)
Interest in the power electronic system which used in many applications is increasing day by day. So, many researchers have focused on the analyses, design and control of these systems. In this study, Optimal for Three Phase Rectifier in Power Electronic System control strategy has been proposed for PSO-PI fuzzy logic controller (FLC) based Three Phase Rectifier in Power Electronic System. Proposed Power Electronic System(PES) consists of input, isolation and output stages. In order to test dynamic performance of PSO-PI based PES, simulation study was carried out by MATLAB/Simulink. The results obtained from the PSO-PI based PES are not only superior in the rise time, settling time and overshoot but can prevent from voltage and has improved power quality.